Taxonomia das espécies de Hyla pertencentes ao grupo de H. Rubicundula Reinhardt & Lutken, 1862 (Amphibia, Anura, Hylidae) - Napoli, Marcelo Felgueiras (1995)
The Hyla rubicundula group is currently composed by three species: H. rubicundula Reinhardt & Lütken. 1862; H. tritaeniata Bokermann. 1965; H. anataliasiasi Bokermann, 1972. We can add to these H. elongata Lutz, 1925, considered junior synonym of H. rubicundula. The absence of strong diagnostic characters among these species makes difficult their accurate identification, making taxonomic studies necessary. With this objective, we have gathered material from several collections, in which we have studied exclusively the external morphology, by characterizing standards of form and pattern and through multivariate morphometrics analysis (multiple discriminant analysis and principal component analysis). The first results provided thirteen morphospecies, for which were analyzed intra- and inter-populational variations. We have found a high degree of intra- and inter-species heteromorphism, which made difficult to establish limits among species. Part of these variation was associated to ontogenetic variation, and part was associated to individual and regional variations. Of these thirteen morphospecies, nine were considered valid species. Hyla elongata had its synonymization to H. rubicundula validated; however, it is necessary to designate a lectotype and paralectotypes for H. elongata, because the description of this taxon was based on material collected at diverse regions and composed probably by more than one species.